Effects of Combined Sorbitan Monolaurate Anti-Agglomerants on Viscosity of Water-in-Oil Emulsion and Natural Gas Hydrate Slurry - Yining Lv; Yintang Guan; Shudi Guo; Qinglan Ma; Jing Gong; Guangjin Chen; Changyu Sun; Kai Guo; Lanying Yang; Bohui Shi; Wei Qin; Yubo Qiao (Energies, 2017)
Hydrate plugging is the major challenge in the flow assurance of deep-sea pipelines. For water-in-oil emulsions, this risk could be significantly reduced with the addition of anti-agglomerants (AAs). Hydrates often form from water-in-oil emulsions and the measurement of emulsion and slurry viscosity constitutes the basis for the application of hydrate slurry flow technology. In this work, using a novel high-pressure viscometer, emulsion and slurry viscosity with different AAs for water content ranging from 5% to 30% was obtained. The viscosity-temperature curves of emulsions were determined and correlated. The variation of system viscosity during hydrate formation from water-in-oil emulsions was examined, the sensitivity of stable slurry viscosity to water cut and the effects of temperature on annealed slurry viscosity were investigated. The results indicated that the variation of viscosity during hydrate formation relies on the conversion ratio. It also implied that the sensitivity of slurry viscosity to change in its water cut or temperature was reduced with AA addition.